The Qurʼan and the universe - Ahmed, Dildar (Paramount Publishing Enterprise Karachi, 2009)
"The Qur'an and the Universe" explores the relationship between the teachings of the Qur'an and the natural world, highlighting how Islamic scripture reflects and aligns with scientific understanding of the universe.